THE ECONOMIC CONCEPT IN THE PERSPECTIVE OF ISLAMIC SUFISM - Dading Zainal Ibrahim; Uus Ahmad Husaeni; Buchori Muslim (Journal of Islamic, Social, Economics and Development, 2023)
The purpose of this article is to analyze how the concept of economics from the perspective of Sufism. The method used in this research is qualitative with a library approach. This article concludes that the economic concept of Sufism is an economic concept in which Sufis view and carry out their economic activities by combining sharia, monotheism, and Ihsan; this characteristic distinguishes the economic activities of Sufis from other societies. From an economic analysis standpoint, through wara, zuhud, and qonaah, thankfulness will create an income distribution that grows the real sector, then increases productivity and employment opportunities, which will drive the economy's pace. This concept will also prevent humans from accumulating wealth (concentrating wealth on a group of people). Of all the core of the economic concept of Sufism, which they emphasize in economic activities, the main goal is to go to Allah SWT. So the economic motive of the Sufis is an expression of obedience to God's commands.